Curcumin Attenuates Asthmatic Airway Inflammation and Mucus Hypersecretion Involving a PPARγ-Dependent NF-κB Signaling Pathway In Vivo and In Vitro. (3rd April 2019) - Zhu, Tao; Chen, Zhihong; Chen, Guihua; Wang, Daoxin; Tang, Shuo; Deng, Huojin; Wang, Jing; Li, Shengjin; Lan, Jian; Tong, Jin; Li, He; Deng, Xinyu; et al.
Abstract : Asthma is characterized by airway inflammation and mucus hypersecretion. Curcumin possessed a potent anti-inflammatory property involved in the PPAR γ -dependent NF- κ B signaling pathway. Then, the aim of the current study was to explore the value of curcumin in asthmatic airway inflammation and mucus secretion and its underlying mechanism. In vivo, mice were sensitized and challenged by ovalbumin (OVA) to induce chronic asthma. Airway inflammation and mucus secretion were analyzed. In vitro, BEAS-2B cells were obtained. MCP-1, MUC5AC, and PPAR γ expression and the phosphorylation of NF- κ B p65 and NF- κ B p65 DNA-binding activity were measured in both the lungs and BEAS-2B cells. shRNA-PPAR γ was used to knock down PPAR γ expression. We found that OVA-induced airway inflammation and mucus hypersecretion in mice, OVA and IL-4-induced upregulation of MCP-1 and MUC5AC, suppression of PPAR γ, and activation and translocation of NF- κ B p65 were notably improved by curcumin both in vivo and in vitro. Our data also showed that these effects of curcumin were significantly abrogated by shRNA-PPAR γ . Taken together, our results indicate that curcumin attenuated OVA-induced airway inflammation and mucus hypersecretion in mice and suppressed OVA- and IL-4-induced upregulation of MCP-1 and MUC5AC both in vivo and in vitro, most likely through a PPAR γ -dependent NF- κ B signaling pathway.